Accelerated Hemolysis and Neurotoxicity in Neuron-Glia-Blood Clot Co-cultures - Jaremko, Kellie M. (2010)
A growing body of experimental evidence suggests that an intracerebral hematoma is toxic to neighboring cells. However, injury mechanisms remain largely undefined, due in part to conflicting results from in vivo studies. In order to investigate blood toxicity in a more controlled environment, murine clots were co-cultured on porous membrane inserts with primary neurons and glia. Erythrocyte lysis was apparent within 48 hours, but was reduced by almost 80% in cultures lacking neurons, and by over 90% in the absence of both neurons and glial cells. By 72 hours, most released hemoglobin had oxidized to methemoglobin or its hemichrome degradation products. At this time point, approximately 50% of neurons were nonviable, as detected by propidium iodide staining; glia were not injured. Deferoxamine, Trolox and the NMDA receptor antagonist MK-801 prevented most neuronal death, but had no effect on hemolysis at neuroprotective concentrations. The 27-fold increase in culture malondialdehyde and 5.8-fold increase in heme oxygenase-1 expression were also attenuated by deferoxamine and Trolox, but not by MK-801. These results suggest that hemoglobin release from clotted blood is accelerated by adjacent neurons and glia. Subsequent neurotoxicity is mediated by both iron-dependent and excitotoxic injury pathways.